Anatomía topográfica del perro: cabeza (2º ejemplar) - Alpízar Moreno, Katherina Michelle (2020)
The objective of this video is to show the dissection of the dog's head, using the dissection protocol created by Dr. Andréia Passos Pequeno and used in the Animal Anatomy laboratory of the School of Veterinary Medicine.